The Influence Of Lectures And Booklet 'Clean Menstruation, Say No To Disease!' On Knowledge, Attitudes, And Menstrual Hygiene Behaviors Among Female Students Of SMK N 1 Kalibagor - Nanda Solikhafi, Helma; Dwi Aprilina, Happy (Jurnal EduHealth, 2023)
Menstrual hygiene is a woman's cleanliness during menstruation to prevent diseases and enhance well-being. Health education is necessary to improve adolescent girls' knowledge, attitudes, and behaviors regarding menstrual hygiene. The study aimed to determine the effect of health education using lecture and booklet methods on the knowledge, attitudes, and behaviors of menstrual hygiene among female SMK Negeri 1 Kalibagor students. This quantitative research used a pre-experimental method. The design employed the one-group pre-post-test design. The sample consisted of 50 female students selected through Probability Sampling and Simple Random Sampling techniques. The research results indicated improved knowledge, attitudes, and behaviors related to menstrual hygiene using lectures and booklets before and after health education. There were differences in knowledge (p=0.00), attitudes (p=0.00), and behaviors (p=0.00) of adolescent girls regarding menstrual hygiene before and after the intervention. The "Clean Menstruation, Disease Goes Away!" booklet has a significant effect on the knowledge, attitudes, and behaviors of female students of SMK Negeri 1 Kalibagor regarding menstrual hygiene.